Transformative visions of legal education/ edited by Anthony bradney and Fiona Cownie - "Bradney , Anthony (ed.)" (Oxford, 1998)
Higher Education institutions around the world are facing a situation of diminishing resources and increasing state inference. How have law schools reacted to this? Is there an increasing movement towards the training of professional lawyers, or is the liberal law degree alive and well? What are the pedagogic concerns of law teachers in this new environment? This volume brings together the work of a number of distinguished scholars who have examined such questions from a number of different perspectives.
Keywords: Law-Higher education